Qualitative elucidation of factors relating to motivation for rehabilitation in convalescent rehabilitation ward inpatient - KYOUGOKU, Makoto; KUWAHARA, Yuya; MORISHITA, Motoyosh; TERAOKA, Mutsumi (Physical Therapy Research in Mental Health, 2025)
Purpose: The purpose of this study was to qualitatively investigate factors related to motivation in highly motivated and low motivated patients admitted to a convalescent rehabilitation ward, and to clarify the relationships between these factors.Methods: The subjects were patients who were hospitalized in a convalescent rehabilitation ward. The method used was the Structure construction qualitative research method. A total of 7 patients with high motivation, and 7 patients with low motivation were interviewed. The data collected from these interviews was analyzed using the Steps for Coding and Theorization.Results: In the high-motivation group, motivation was influenced by the synergistic effects of patient factors, therapist factors, and third-party factors. This structure reduced the negative experiences caused by hospitalization, which were a factor that reduced motivation. In the low-motivation group, patient factors, therapist factors, and third-party factors had mutual effects on motivation to undergo rehabilitation. These factors counteracted motivation-promoting factors.Conclusion: This study found that in both groups, motivation for rehabilitation does not belong only to the individual patients, but is created by the interactions between the patient, the people around them, and the circumstances surrounding them.